Stiripentol exhibits higher anticonvulsant properties in the immature than in the mature rat brain. Issue 12 (10th October 2013) - Auvin, Stéphane; Lecointe, Cécile; Dupuis, Nina; Desnous, Béatrice; Lebon, Sophie; Gressens, Pierre; Dournaud, Pascal
Summary Purpose After the first positive experimental data in rodents in the early 1970s demonstrating the anticonvulsant effect of stiripentol (STP), in vitro studies showed that STP acts directly on γ‐aminobutyric acid A (GABAA) receptors. Chloride influx is higher when these receptors contain an α3 subunit, leading to the hypothesis that STP might exhibit higher efficacy in the immature brain. Methods We explored this issue by studying the efficacy of STP in P21 and P75 rats using the pentylenetetrazol model of acute seizures or the lithium‐pilocarpine status epilepticus model. P21 and adult rats received vehicle, 150, 250, or 350 mg/kg of STP, i.p., 1 h before evaluating the anticonvulsant. We also studied the blood and brain levels of STP as well as the expression and the messenger RNA (mRNA) levels of the α3 subunit of the GABAA receptors at both ages. Keys Findings STP exhibited anticonvulsant properties in both models at both ages, but STP was more effective in P21 than in P75 rats. This was shown by the significant suppression of seizure or status epilepticus occurrence in P21 with 350 mg/kg STP, whereas the same dose had no significant effect at P75. The blood level, brain level, and blood/brain ratio of STP did not explain these differences between the two age groups. Moreover, the higher anticonvulsant properties in the immature brain were not explained by the mRNA level or protein expression of the GABAA α3 subunit at either age. Significance Stiripentol exhibits higher anticonvulsant properties in the immature than in the mature brain. These findings require further investigation because it might lead to new clinical developments.